1977
DOI: 10.1111/j.1365-2389.1977.tb02273.x
|View full text |Cite
|
Sign up to set email alerts
|

THE USE OF MOUNDS OF THE TERMITE MACROTERMES FALCIGER (GERSTÄCKER) AS A SOIL AMENDMENT

Abstract: Twelve termite mounds and adjacent Ah and Ap horizons were sampled at three sites near Salisbury, Rhodesia. The mass of termite mounds occupied by M. fulciger at one site was estimated at 620 tlha, and contained the following amounts of nutrients expressed as percentages of the amounts in mounds and Ap horizon combined: extractable Ca 9570, mineral N 81% extractable K 69%, and available P 69%.Pot experiments using perennial ryegrass gave higher dry matter yields from termite mounds than from the Ap and Ah hori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 7 publications
1
44
1
Order By: Relevance
“…The accumulation of nutrients in termite mounds, both through the concentration and subsequent decomposition of organic matter (Jones 1989), and through the concentration of minerals in groundwater by evaporation within the mounds and chimneys (Weir 1973), produces nutrient-rich patches within an otherwise nutrient-poor landscape. Mound soils have significantly higher total N, acidextractable P and basic cation levels than surrounding soils (Trapnell et al 1976;Watson 1977;Jones 1989).…”
Section: Termites Fire and Nutrient Cyclingmentioning
confidence: 96%
See 1 more Smart Citation
“…The accumulation of nutrients in termite mounds, both through the concentration and subsequent decomposition of organic matter (Jones 1989), and through the concentration of minerals in groundwater by evaporation within the mounds and chimneys (Weir 1973), produces nutrient-rich patches within an otherwise nutrient-poor landscape. Mound soils have significantly higher total N, acidextractable P and basic cation levels than surrounding soils (Trapnell et al 1976;Watson 1977;Jones 1989).…”
Section: Termites Fire and Nutrient Cyclingmentioning
confidence: 96%
“…The vegetation on the mounds is often the focus of activity for birds and other animals, enabling these species to exist in an otherwise largely unproductive environment. In addition, soil from termite mounds is widely used by farmers as an amendment to their fields (Watson 1977).…”
Section: Termites Fire and Nutrient Cyclingmentioning
confidence: 99%
“…It therefore seems possible for local farmers to use the mound debris, especially the nest body parts, as a soil amendment, as proposed by Watson (1977), Dangerfield et al (1998) and Duponnois et al (2005). In particular, the use of termite debris would have a beneficial effect on crop growth in K-deficient soils and sandy soils such as savanna soils in the Basement Complex area of West Africa (e.g., , since they have very high levels of exchangeable K and clay.…”
Section: Soil Properties In Termite Moundsmentioning
confidence: 99%
“…A comparison with surrounding surface soils (Lobry de Bruyn and Conacher, 1990;Black and Okwakol, 1997) shows that the soil material that constitutes termite mounds often accumulates some nutrients along with clay particles. This association of nutrients with large mounds of Macrotermes termites is why some researchers have suggested that subsistence farmers use termite mound debris as soil amendments in low-input cropping systems (Watson 1977;Dangerfield et al 1998;Duponnois et al 2005). From an ecological point of view, termite mounds and the eroded material from these mounds often create nutrient patchiness that leads to ecological hot spots in nutrient-depleted tropical savanna soils (Salick et al 1983;Obi and Ogunkun 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Usually high concentration of organic matter and mineral nutrients are found in termite mound than in the surrounding soils. Consequently, subsistence farmers in Africa commonly spread termite mound materials in their fields to improve soil conditions and increase plant nutrient availability [10,11]. They also promote nutrient availability, nutrient cycling and soil physical properties [8].…”
Section: Introductionmentioning
confidence: 99%